2023
DOI: 10.4314/jae.v27i1.2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Agricultural Extension Services on Cereal Production among Rural Farmers in Bhutan

Abstract: This study explored the impact of agricultural extension services on cereal production. Data were collected through a semi-structured questionnaire from a random sample of 262 farmers from four regions (east, west, north, and south) in Bhutan. Farmers assessed the impact of extension services on five aspects of cereal production (cereal seed, social, environmental, production, and marketing aspects). Percentages and an ordered logistic model were used to analyse the data. The study found a low level of farmers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
1
1
Order By: Relevance
“…This implies that as the size of rice-cultivated land increases by one hectare, the likelihood of receiving extension services decreases by approximately 11.8%. This finding contradicts the results reported by [9], which demonstrated a significant and positive influence of cultivated land size on receiving extension services at the 10% significance level. These conflicting results suggest that the relationship between cultivated land size and the receipt of extension services may vary across different studies or contexts, as mentioned in the work of [45].…”
Section: Drivers Of Receiving Agricultural Extension Servicecontrasting
confidence: 99%
See 1 more Smart Citation
“…This implies that as the size of rice-cultivated land increases by one hectare, the likelihood of receiving extension services decreases by approximately 11.8%. This finding contradicts the results reported by [9], which demonstrated a significant and positive influence of cultivated land size on receiving extension services at the 10% significance level. These conflicting results suggest that the relationship between cultivated land size and the receipt of extension services may vary across different studies or contexts, as mentioned in the work of [45].…”
Section: Drivers Of Receiving Agricultural Extension Servicecontrasting
confidence: 99%
“…One of the drawbacks of a centralized extension service is that it can lead to weak linkages between smallholder farmers' needs and the extension service itself. This can result in a lack of responsiveness to the specific challenges and context faced by smallholder farmers [9]. The shift towards a pluralistic agricultural extension system, as noted in [2] and other literature, is driven by the recognition that no single actor or approach can effectively address the diverse needs and complexities of agricultural systems.…”
Section: Introductionmentioning
confidence: 99%
“…Any mean greater than 2.99 is considered high while below is considered low. The result indicates that farmers were introduced to different capacitybuilding programme but their participation was low , which might have affected cocoa production level This is in line with the finding of Shangshon, et al, 2023 who reported low participation of farmers in agricultural extension activities were low According to Kassem et al, 2021, low participation could be attributed to lack of awareness., the ineffectiveness dissemination methods of various services, farmers' inability to attend meetings, wrong timing, poor teaching aids, or poor communication strategies. However, Farmers Field School has been of more value to the farmers because according to Henk van den Berg et al (2020) FFS impacts human capital and the social lives of the farmers therefore, in order to increase participation constraints to their participation must be dealt with.…”
Section: Level Of Participation Of the Farmers In The Management Trai...supporting
confidence: 77%
“…The most frequently used communication of Nigeria's Oyo State extension workers consists of farmer contacts, farm visits, and home visits (Yekinni & Afolabi, 2019). Therefore, improving extension services effectively and of high quality is essential, as it can help smallholders increase their agricultural production (Shangshon et al, 2023). Finally, the role of extension workers is not only carried out by government institutions, but there is a partial shift in the role of private agricultural extension workers to public or farmer organizations or private institutions (Chand & Kumar, 2019).…”
Section: The Role Of Agricultural Extension Workers In the Implementa...mentioning
confidence: 99%